The significance of dynamic monitoring plasma TMAO level in pulmonary arterial hypertension – a cohort study - Yicheng Yang; Xin Li; Peizhi Wang; Songren Shu; Bingyang Liu; Yanru Liang; Beilan Yang; Zhihui Zhao; Qin Luo; Zhihong Liu; Lemin Zheng; Qixian Zeng; et al. (Therapeutic Advances in Respiratory Disease, 2024)
Background: Gut microbiota assumes an essential role in the development and progression of pulmonary arterial hypertension (PAH). Trimethylamine N-oxide (TMAO), a gut microbiota-dependent metabolite, is correlated with the prognosis of patients with PAH. However, the correlation between changes in TMAO (ΔTMAO) and the prognosis of PAH remains elusive. Objectives: To investigate the association between ΔTMAO and prognosis of PAH, and explore whether dynamic assessment of TMAO level was superior to measurement at a single time point in predicting prognosis. Design: Single-center cohort study. Methods: Consecutive patients diagnosed with PAH and had at least two TMAO measurements taken from May 2019 to June 2020 were eligible. The outcome events of this study were defined as adverse clinical events. Results: A total of 117 patients with PAH who had two TMAO measurements and follow-up were included in this study. Patients with ΔTMAO ⩾1.082 μmol/L had over four times increased risk of adverse clinical events than their counterparts after adjusting for confounders [hazard ratio (HR) 4.050, 95% confidence interval (CI): 1.468–11.174; p  = 0.007]. Patients with constant high TMAO levels at both time points had the highest risk of adverse clinical events compared with patients with constant low TMAO levels (HR 3.717, 95% CI: 1.627–8.492; p  = 0.002). ΔTMAO was also associated with changes in parameters reflecting PAH severity ( p  < 0.05). Conclusion: Changes in TMAO were independently correlated with prognosis in patients with PAH, irrespective of baseline level of TMAO. ΔTMAO also correlated with alteration in disease severity. Repeated assessment of TMAO level contributes to better identification of patients with increased risk of adverse clinical events.